2011
DOI: 10.1016/j.otsr.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular osteoid osteoma of the hip misdiagnosed by MRI: An unusual cause of unexplained hip pain

Abstract: Osteoid osteoma is a common benign bone tumor affecting the young adult with typical clinical and radiographic presentation in its most common locations. However, when arising in unusual intra-articular locations, diagnosis may appear confusing and lead to delayed management. We present the case of a 24-year-old man with intra-articular osteoid osteoma of the hip involving the posteroinferior quarter of the femoral head. This unusual location was at the origin of unexplained pain and delayed diagnosis made 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
17
0
5
Order By: Relevance
“…In addition, an atypical presentation of the nidus may lead to misdiagnosis. 18,19 Bone scintigraphy is a highly sensitive imaging modality. However, it shows a lower specificity than a CT scan particularly in case of intra-articular OO because of the associated synovial reaction location causing less intense uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an atypical presentation of the nidus may lead to misdiagnosis. 18,19 Bone scintigraphy is a highly sensitive imaging modality. However, it shows a lower specificity than a CT scan particularly in case of intra-articular OO because of the associated synovial reaction location causing less intense uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Initially plain X-rays are the modality of choice due to the relatively low cost and radiation exposure, but the diagnostic yield is far superior with CT. [23][24][25] The potential advantage of MRI over CT is in decreased radiation exposure, particularly to the paediatric patient, but the diagnostic accuracy has been shown to be inferior. 26,27 Hosalkar et al found MRI only had a 19% (7/36) accuracy in diagnosing OO, while all lesions in this series were accurately diagnosed pre-operatively on fine cut CT imaging. 28 The use of gadolinium enhancement in MRI scanning may improve diagnostic accuracy but this increases cost and it has not been shown to be superior to CT. 29 In our series, CT was more accurate in diagnosing OO; four of the five patients with an OO had an inconclusive MRI but went on to have a CT that accurately diagnosed OO.…”
Section: Discussionmentioning
confidence: 53%
“…However, pain related to osteoid osteoma does not always worsen at night and is not always relieved by nonsteroidal antiinflammatory drugs (in particular, acetylsalicylic acid), especially when it occurs in intraarticular locations [5][6][7][8]18]. As a result, patients are treated conservatively, and physi-cians who have been misled by nonspecific radiographic findings refer patients for MRI examination.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first to describe a way to identify osteoid osteoma of the femoral neck just by recognizing the appearance of bone marrow edema on coronal STIR and axial fat-suppressed T2weighted turbo spin-echo images without the need for optimization of MRI technique [6,[11][12][13]. We have used the term "half-moon sign" to describe the half-disc appearance of bone marrow edema in cases of osteoid osteoma of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%